2021
DOI: 10.1111/nep.13952
|View full text |Cite
|
Sign up to set email alerts
|

Association between conscientiousness and peritoneal dialysis‐related peritonitis

Abstract: Aim: Peritonitis is a critical complication in patients undergoing peritoneal dialysis.Patient characteristics, especially conscientiousness, potentially influence self-care activity. This study aimed to examine the relationship between the peritonitis risk and the patient conscientiousness.Methods: This retrospective observational study was conducted at three Japanese medical centres in 2018. Adult patients undergoing peritoneal dialysis were evaluated for conscientiousness with the Japanese version of the Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…It can ultimately improve the prognosis of patients by affecting their daily behaviors such as dietary patterns, medication habits, and PD procedures. Early studies by Japanese scholars [ 14 ] have revealed a close relationship between conscientiousness and peritonitis in PD patients. Our research also demonstrates that peritonitis risk is much higher in PD patients with lower conscientiousness scores than in those with higher conscientiousness scores.…”
Section: Discussionmentioning
confidence: 99%
“…It can ultimately improve the prognosis of patients by affecting their daily behaviors such as dietary patterns, medication habits, and PD procedures. Early studies by Japanese scholars [ 14 ] have revealed a close relationship between conscientiousness and peritonitis in PD patients. Our research also demonstrates that peritonitis risk is much higher in PD patients with lower conscientiousness scores than in those with higher conscientiousness scores.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that conscientiousness is a dutiful, achievement-oriented, orderly, and accepting of the rules trait [ 80 ], and therefore, people having this trait may show greater compliance with self-care activities and risk of diabetes [ 75 , 81 , 82 ]. Many other individual studies of people with chronic conditions other than diabetes consistently also found positive health benefits of being highly conscientious [ 76 , 83 - 85 ]. The observed results are also consistent with the conclusions of a systematic review that included 17 studies of adults with type 2 diabetes and found weak to moderate associations between weight management and personality traits such as neuroticism and conscientiousness [ 73 ].…”
Section: Reviewmentioning
confidence: 99%